Pengaruh Growth Mindset terhadap Kesiapan Melakukan Perubahan pada Dosen di Jawa Barat - Indah Puspitasari (Humanitas (Jurnal Psikologi), 2023)
The aim of this study was to analyze the roles of mindset on the readiness to change of lecturers in West Java. All organizations will surely face change without exception including universities. Many changes are happening rapidly in the education field. Change will not success and fulfill its goals if human resources as change drivers are not ready to change. For this reason, it is important to know the readiness to change of lecturers in West Java in dealing with changes that occur in the current environment and in the future. Readiness to carry out this change is associated with the individual mindset in the organization. Population in this  research  was lecturers in West Java. Sampling was done by purposive sampling technique with the criteria of having worked for at least 1 year as a lecturer. The number of research samples is 156 people. The data collection method was carried out through a survey by providing a Mindset Scale and Readiness to Change Scale compiled by the researcher. The Mindset Scale Reliability was 0.749 and the Readiness to Change Scale was 0.904. The results of the analysis show that the mindset variable contributes an R value of 0.334 (p <0.05) to readiness for change, with a coefficient of determination (R2) of 0.112 or 11.2%.